Comparative Study of Indonesian Pre-Service Teachers’ Challenges and Strategies in Thailand and Australia - Nuraini, Hanifa (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
International teaching practicums are vital for teacher education, offering pre-service teachers (PSTs) transformative experiences that vary significantly by host country. This qualitative comparative case study fills a literature gap by examining the challenges and coping strategies of two Indonesian English Education PSTs, Anita (Australia) and Anto (Thailand). This study applied Searle and Ward’s (1990) two-domain model of cross-cultural adaptation. Data, collected through in-depth, semi-structured interviews and supplementary documents, were analyzed using comparative thematic analysis. Findings show that while both participants achieved significant professional growth, their main challenges and adaptation routes differed based on the host country’s developmental, linguistic, and cultural context. Anita, in a developed, English-speaking country, Australia, primarily faced systemic and academic hurdles, such as formal curriculum standards (AITSL) and initial difficulty understanding English accents. Her adaptation, supported by a mentor from a similar background, greatly improved her English speaking confidence. On the other hand, Anto, in a developing, non-English-speaking country, Thailand, struggled with language barriers both in daily life and professional situations, along with significant culture shock. His adaptation, supported by two mentors and support from peers, helped him become highly adaptable and culturally aware by actively engaging with new languages and social settings. The study concludes that the specific institutional, linguistic, and cultural conditions of the host country are closely linked to how sociocultural and psychological challenges emerge, and they shape the most effective coping strategies for pre-service teachers.